Evaluating floor types during simple composting of leaf wastes - Elhamida Rezkia Amien; Ridwan Baharta; Muhammad Yusfiar Karfiandi; Liska Mutiara Septiana; Mareli Telaumbanua; Agus Haryanto (Brawijaya University, 2023)
This study aimed to evaluate the type of floor in the composting process of leaf wastes. The waste consisted of cacao leaves (Theobroma cacao L.), rubberwood leaves (Hevea brasiliensis), teak leaves (Tectona grandis L.f), matoa or Fijian longan leaves (Pometia pinnata), durian leaves (Durio zibethinus), and grass. The research was conducted by composting the leaf mixtures in a composting box sizing 220 cm in length, 180 cm in width, and 100 cm in height. A long box was partitioned by using plastic tarpaulin into four boxes for different floors, namely cement, soil, tarpaulin, and rice husks. A mixture of leaves of 127 kg to 176 kg was introduced in each box and was composted for 145 days. Variables observed were temperature, the height of heap, the mass of material (initial and final), C/N ratio, NPK contents, compost color, odor, pH, and moisture content. The results showed that compost quality fulfilled Indonesian National Standard (SNI 19-7030-2004) regardless of the floor types. However, the type of floors affected the compost process and yield. The composting process with tarpaulin-layered or husk-layered floors produced better compost in terms of N, P, C/N ratio, and color as compared to those resulting from cemented or barely soil floors.